2006
DOI: 10.1051/0004-6361:20065341
|View full text |Cite
|
Sign up to set email alerts
|

First observations with CONDOR, a 1.5 THz heterodyne receiver

Abstract: Context. The THz atmospheric "windows", centered at roughly 1.3 and 1.5 THz, contain numerous spectral lines of astronomical importance, including three high-J CO lines, the [N II] line at 205 µm, and the ground transition of para-H 2 D + . The CO lines are tracers of hot (several 100 K), dense gas; [N II] is a cooling line of diffuse, ionized gas; the H 2 D + line is a non-depleting tracer of cold (∼20 K), dense gas. Aims. As the THz lines benefit the study of diverse phenomena (from high-mass star-forming re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…CONDOR employs a closedcycle PT cryocooler and solid-state LO sources manufactured by Radiometer Physics GmbH and Virginia Diode, Inc. With CONDOR, observations of high-J CO lines, the transition line of [N II], and the ground transition of para-H 2 D + , which are good tracers of hot dense gas, ionized diffuse gas, and cold dense gas, respectively, were demonstrated toward Orion FIR4 in 2006 [52]. The University of Tokyo group started astronomical observation by installing their own 0.9-and 1.3-THz-band waveguide-type NbTiN HEB mixers onto the 10-m Atacama Submillimeter Telescope Experiment (ASTE) located at Pampa La Bola in northern Chile (at an altitude of 4860 m) in 2011 [19].…”
Section: Observations With Heb Mixersmentioning
confidence: 99%
“…CONDOR employs a closedcycle PT cryocooler and solid-state LO sources manufactured by Radiometer Physics GmbH and Virginia Diode, Inc. With CONDOR, observations of high-J CO lines, the transition line of [N II], and the ground transition of para-H 2 D + , which are good tracers of hot dense gas, ionized diffuse gas, and cold dense gas, respectively, were demonstrated toward Orion FIR4 in 2006 [52]. The University of Tokyo group started astronomical observation by installing their own 0.9-and 1.3-THz-band waveguide-type NbTiN HEB mixers onto the 10-m Atacama Submillimeter Telescope Experiment (ASTE) located at Pampa La Bola in northern Chile (at an altitude of 4860 m) in 2011 [19].…”
Section: Observations With Heb Mixersmentioning
confidence: 99%
“…Previous studies have also demonstrated improved stability by stabilizing the incident LO power in an HEB [5][6][7][8][9][10]. However until now, they have been either frequency or LO-source specific.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Balanced waveguide HEB mixers have demonstrated improved stability 11 but at the expense of complex device design and fabrication. Furthermore, it has been shown that it is possible to stabilize an HEB mixer by stabilizing the amplitude of a far infrared (FIR) gas laser LO by adding electrical feedback to its CO 2 pumping laser.…”
mentioning
confidence: 99%